Indications and Common Complications of Caesarean Section: An Overview Study (Eurasian Medical Research Periodical, 2021)
A cesarean section involves delivery of the fetus by doing surgical incision in the women abdomen (laparotomy) and an incision in the uterine cavity (hysterotomy). On a large scale around the world, the incidence of caesarean sections is high if compared to natural birth, which makes the possibility of exposure to health complications that is result from caesarean birth is somewhat high. On the other hand, the complications that may accompany a woman who is undergoing a caesarean section differ according to the several a circumstances which is surrounding those women such as age, health status, previous medical history, family history and follow-up by the health team in the hospital. For some women, a cesarean delivery can be the safest or even the only way to deliver a healthy baby